ANALYSIS OF LANGUAGE ERRORS IN ONE OKEZONE MEDIA JOURNALISTIC PRODUCT - Anjani Lintang Pertiwi; Aulia Afifah; Vanessa Viviana Shodiq; Aveny Septi Astriani (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This research is motivated by language errors due to a lack of understanding of the language used, and inappropriate or imperfect language teaching often occurs in the mass media. The method used in this research is a descriptive method because in this research it analyzes and examines a research data object according to the facts. The data collection technique is by reading and analyzing language errors from the text. The data collection instruments used were a feature text entitled "4 OOTD Inspirations during the Rainy Season, Stay Cool and Warm" and stationery. Then, the data analysis techniques in this research include: (1) reading the feature text "4 OOTD Inspirations during the Rainy Season, Stay Cool and Warm"; (2) analyzing language errors in the text; (3) write down the analysis results obtained. This research is useful in providing in-depth insight into language errors that are often found in various mass media.